Privacy Enhancing Technologies 11th International Symposium, PETS 2011, Waterloo, ON, Canada, July 27-29, 2011, Proceedings - Fischer-Hübner, Simone; Hopper, Nicholas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
This book constitutes the refereed proceedings of the 10th International Symposium, PETS 2011, held in Waterloo, Canada, in July 2011. The 15 revised full papers were carefully reviewed and selected from 61 submissions. The papers address design and realization of privacy services for the Internet, other data systems and communication networks. Presenting novel research on all theoretical and practical aspects of privacy technologies, as well as experimental studies of fielded systems the volume also features novel technical contributions from other communities such as law, business, and data protection authorities, that present their perspectives on technological issues.
Keywords: Data encryption (Computer science).; Computer communication systems; Computer security; Management information systems; Computer science; Computers and civilization; Algorithms; Cryptology; Computer Communication Networks; Systems and Data Security; Management of Computing and Information Systems; Computers and Society; Algorithm Analysis and Problem Complexity